Factors Influencing Urban and Rural Women’s Access to Financial Inclusion in Belize - Ramclam, Tanya; Arulanandam, Benedict Valentine; Kárpáti, József; Kumarasamy, Mokana Muthu; Dávid, Lóránt Dénes (Journal of Cultural Analysis and Social Change, 2025)
The primary objective of this research is to delve into the intricate realm of women's financial inclusion and the multifaceted impediments hindering such inclusion within the Belizean context. Furthermore, this study endeavors to define various methodologies aimed at strengthening women's financial inclusion, exploring initiatives such as heightened financial literacy programs, expanded access to formal credit for women-led enterprises, governmental loan schemes, personalized microfinance endeavors tailored to women, as well as advocating for the enactment of legislation that prohibits gender-based discrimination. Drawing upon an extensive array of published data over the period from 2005 to 2022, this investigation meticulously examines the correlation between gender equality and financial inclusion and stability. The findings uncover a convincing narrative, explaining the pivotal role of gender parity in fostering financial inclusivity and stability within the socio-economic realm of a developing nation. Furthermore, this study theorizes that fostering gender equality could serve as an effective promoter for enhancing Belize's financial inclusion and resilience in the face of economic uncertainties.